Causes and Consequences of Pre-Marital Sex among Female Students of Oke-Ogun Polytechnic in Oyo State, Nigeria - BOLU-STEVE, Foluke Nike; AJIBOYE, Samuel Kolawole; FADIPE, Rasaq Abimbola (Ilorin Journal of Education, 2023)
Premarital sex is a source of concern among female students in tertiary institutions of learning particularly in Oke-Ogun Polytechnic of Oyo state, Nigeria. The study, therefore, investigated causes and consequences of premarital sex among female students of Oke-Ogun polytechnic, Oyo state. Researchers-developed instrument tagged “Causes and Consequences of Premarital Sex Questionnaire (CCPSQ)” was used to collect the data. Two hundred and fifty respondents participated in the study, and simple random sampling technique was used to select the participants. The findings of the study revealed that negative peer pressure, cohabitation and sexual harassment were the major causes of premarital sex, while the study also revealed that unsafe abortion, school dropout and unwanted pregnancy were the major consequences of premarital sex among respondents. The study thus recommended that school counsellors should constantly be in contact with female students to educate them on sexuality and how best to manage their sexual feelings without necessarily engaging in premarital sex. School authorities should use media means to counsel female students on the causes and consequences of premarital sex. Health educators should rise to the challenge of organising enlightenment activities in schools in order to provide adequate reproductive health information to female students.